Incarceration and fatherhood: adapting to the change - Brown, Michael A.; Nelson, Ashley E. (My University, 2011)
Father involvement plays an important role in the development of children, and for fathers who are incarcerated this presents challenges that seem insurmountable (Sarkadi, Kristiansson, Oberklaid, & Bremberg, 2008; Arditti, Smock & Parkman, 2005). The sites of this cross-sectional and nonrandom pilot study were at two Northwestern Wisconsin county jail facilities with 52 participants. Incarcerated fathers were surveyed on maintaining involvement with their children during incarceration. We hypothesized fathers who had a positive relationship with their children and the caretaker before incarceration would have higher levels of involvement during incarceration. Survey data were statistically analyzed using frequencies, mean-comparisons, correlations, and a Cronbach's Alpha reliability analysis. Variables that dealt with having a good relationship with the primary caregiver and involvement with the children through visitations and contact with children at least weekly showed there was a significant correlation. Implications for practitioners are that current correctional facility policies and correctional staff limit fathers' involvement in the lives of their children; facilities need to improve access to support father-child involvement. Future research would benefit by having a large, randomized national sample and a more appropriate survey reading level, as well as qualitative interviews.
Keywords: Children of prisoners--Wisconsin; Male prisoners--Family relationships--Wisconsin; Parenting--Wisconsin; Fatherhood--Wisconsin